Comparing agility and shadow training with core stability at riau specialized sports school - Fahrul Fahrozi; Bafirman Bafirman; Donie Donie; Ridho Bahtra; Fiky Zarya; Rahmad Diyanto (Global Econedu, 2026)
This study aims to determine the effect of agility training incorporating core stability and shadow training incorporating core stability on the improvement of badminton footwork at the Riau Specialised Sports School (SKO). This is a quasi-experimental study, employing a “two-groups pre-test-post-test design”. The population for this study comprised 26 athletes from the Riau SKO, with the sample selected using purposive sampling: male athletes who were still active at the Riau SKO and had chosen badminton as their sport, totalling 12 male athletes aged 16-18 years. The instrument used in this study was a 30-second badminton footwork test. The data analysis techniques for hypothesis testing utilised the Paired Sample Test and the Independent Sample Test. The results of the study indicate: Firstly, there is a significant effect of agility training combined with core stability on the improvement of footwork in badminton at SKO Riau, with a significance level (2-tailed) of 0.000 < 0.05. Secondly, there was a significant effect of shadow training combined with core stability on the improvement of footwork in badminton at SKO Riau, with a significance level (two-tailed) of 0.003 < 0.05. Thirdly, there was no difference in the mean effect between the agility training with core stability group and the shadow training with core stability group on the improvement of footwork in badminton at SKO Riau, with a significance value (two-tailed) of 0.277 > 0.05.